Metabolic engineering of medium-chain fatty acid biosynthesis in Nicotiana benthamiana plant leaf lipids - Reynolds, Kyle B.; Taylor, Matthew C.; Zhou, Xue-Rong; Vanhercke, Thomas; Wood, Craig C.; Blanchard, Christopher L.; Singh, Surinder P.; Petrie, James R. (Frontiers in Plant Science, 2015)
Various research groups are investigating the production of oil in non-seed biomass such as leaves. Recently, high levels of oil accumulation have been achieved in plant biomass using a combination of biotechnological approaches which also resulted in significant changes to the fatty acid composition of the leaf oil. In this study, we were interested to determine whether medium-chain fatty acids (MCFA) could be accumulated in leaf oil. MCFA are an ideal feedstock for biodiesel and a range of oleochemical products including lubricants, coatings and detergents. In this study, we explore the synthesis, accumulation and glycerolipid head-group distribution of medium-chain fatty acids (MCFA) in leaves of Nicotiana benthamiana after transient transgenic expression of C12:0-, C14:0- and C16:0-ACP thioesterase genes. We demonstrate that the production of these MCFA in leaf is increased by the co-expression of the WRINKLED1 (WRI1) transcription factor, with the lysophosphatidic acid acyltransferase (LPAAT) from Cocos nucifera being required for the assembly of tri-MCFA TAG species. We also demonstrate that the newly-produced MCFA are incorporated into the triacylglycerol of leaves in which WRI1 + diacylglycerol acyltransferase1 (DGAT1) genes are co-expressed for increased oil accumulation.